APLIKASI âPASOPATIâ DALAM UPAYA PENANGGULANGAN BAHAYA KEBAKARAN DI INDUSTRI DAN PERUMAHAN - Indriani, Siti Nurlaila; Purwito Aji, Mareta Danar; Santosa, Hardi; Nugroho, Rio Aji; Aditya, Rezhaa (Program Kreativitas Mahasiswa - Teknologi, 2014)
Fire is a disaster that can happen anytime and anywhere. Real measurement of the fire problem is that it generates a loss. Such losses may be direct or indirect damage that can not be repaired. Many companies that went bankrupt after the great fire, although the company has sufficient insurance to cover the losses, as the company was unable to regain market share lost when the factory shut down. Therefore, developed a tool PASOPATI, Portable Automatic Water Foam Monitor is easy and safe to operate. ATMega 32 is used as a control that is able to receive instructions from the remote control and additional motor driver for controlling the movement of the tool. The result is a tool PASOPATI can be controlled with a remote control with a distance of about 50 meters, so that the safety of the operator is awake and able to optimize operator firefighters to evacuate the victims. Pasopati tool can assist in putting out the fire in order to prevent greater losses due to fire.Keyword : Pasopati, Automatic, Portable Water foam, Water foam